(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
The trend of smoking among women is rising in some developing countries. The objective of this population-based cross-sectional study was to determine the sociodemographic risk factors of cigarette smoking among Iranian women of reproductive age. A total of 1359 women were randomly selected for the study. Multivariable logistic regression analysis was used to estimate the adjusted association between sociodemographic variables and cigarette smoking. The odds of cigarette smoking were higher among divorced women (OR [odds ratio]: 14.0; 95% CI [confidence interval]: 4.1–47.3) and women with a university education (OR: 2.6; 95% CI: 1.3–5.0). This study highlights an association between marital status and education with cigarette smoking among Iranian women.